Hubungan suami perokok terhadap bayi berat lahir rendah pada neonatus di ruang Perinatologi RSUD Wangaya kota Denpasar - William Grandinata Soeseno; I Wayan Bikin Suryawan; A.A. Made Widiasa (Intisari Sains Medis, 2019)
Background: Low birth weight babies (LBW) are still a problem. The causes of LBW are multifactorial, one of which is exposure to toxic substances (cigarettes). Exposure to cigarette smoke can disrupt fetal development during the womb. Based on studies, active and passive smokers have almost the same level of risk. This study aimed to find out about a smoker's husband as a risk factor for the occurrence of low birth weight babies in neonates at Perinatology Room of Wangaya Hospital, Denpasar.Methods: Analytical observational research with case-control research design. The study sample was all neonates who were treated in the Perinatology Room of Wangaya Hospital from May to August 2018 and fulfilled the inclusion and exclusion criteria. Based on the calculation of the sample size, 72 neonates were obtained. The sample is determined by consecutive sampling. In this study, data were obtained from medical records (documentation) and questionnaires.Result: Samples were divided into two groups, namely the case group and controls where each group consisted of 36 samples. As many as 23 of the 36 neonates who were smokers' husbands suffered from low birth weight babies (63.88%), while 13 others did not suffer from low birth weight babies (36.11%). The results of hypothesis testing using the chi-square test, the value of p = 0.03 (p < 0,05, OR = 2,78, CI = 0,091-0,267).Conclusion: Smokers' husbands were significantly a risk factor for the occurrence of low birth weight babies in neonates who were treated in the Perinatology room of Wangaya Hospital, Denpasar.